Comparison of different methods for predicting the drift angle and rudder resistance by wind propulsion systems on ships. (1st December 2020) - Elger, David E.; Bentin, Marcus; Vahs, Michael
Abstract: To address climate change, innovative ships with alternative propulsion systems must be developed to reduce greenhouse gas emissions. One option is to use additional wind propulsion systems, which encounter additional resistance due to drift and rudder forces. After calculating the sail forces, changing the locations of the aerodynamic centre of pressure of the sails and the centre of lateral resistance on the hull depending on the ship's speed and drift angle has a significant influence. The aim of this research is to show how the drift and rudder angles and the corresponding forces can be calculated using methods from Skogman, Wagner, Bertram, Lewis, and Larsson. The drift calculation methods are validated using the results from tank towing model tests in oblique flow with a traditional sailing vessel and a multi-purpose vessel. A comparison of theoretically calculated and measured drift forces as well as the prediction of the drift angle by Skogman's method show good agreement when the pressure points are close enough to each other. Additionally, the methods for calculating the rudder forces by Bertram, Lewis, and Larsson are sufficient for use in further investigations. Highlights: Describes how a force and moment equilibrium is set up for a ship with sails. Shows an algorithm for how to find the ship's speed under sails including drift and rudder. Derives a method for calculating the drift angle and the corresponding added resistance. Compares different methods for calculating the rudder angle and resistance. Includes verification with model test results from two different kinds of ships.